Civil Registration Awareness, Compliance, Purpose, and Challenges among Municipal Residents in the Philippines - Jeremy G. Celeste; Merlita V. Caelian (Philippine Social Science Journal, 2021)
Civil registration aims to secure permanent records of people. In the Philippines, Republic Act No. 3753 or the Civil Registry Law mandates that all vital events should be registered. This study aims to assess the civil registration awareness, compliance, purpose, and challenges of municipal residents in Negros Occidental, Philippines. A descriptive-comparative and correlational study was used through a researcher-made questionnaire among 376 residents of villages identified using stratified random sampling. The study revealed that the level of awareness of the residents on civil registration is high. At the same time, the extent of compliance was high on birth and marriage but low on death registration. It also revealed a significant difference between awareness and compliance on civil registration when respondents are grouped according to sex and educational attainment, but no significant differences when grouped as to age, income, and distance to the office of the local civil registrar.  There is a significant relationship between the level of awareness and extent of compliance in the civil registration of residents. Among the challenges for nonregistration or delayed registration of vital events are lack of valid identification card and high cost of transportation, among others.